Workshop Slave Trade Memories: A conversation with Kangni Alem (A Conversation with ..., 2023)
Kangni Alem is a writer, translator and literary critic, playwright, art collector and exhibiton curator, director of the "Atelier Théâtre de Lomé" founded by him in 1989. He has received numerous awards, including the Grand prix littéraire d'Afrique noire for his book Cola Cola jazz. He was part of the workshop "slave trade memories at the crossroads of literature, performance and history".